Rethinking Iranian nationalism and modernity - Aghaie, Kamran Scot; Marashi, Afshin (University of Texas Press, 2014)
While recent books have explored Arab and Turkish nationalism, the nuances of Iran have received scant book-length study - until now. Capturing the significant changes in approach that have shaped this specialization, Rethinking Iranian Nationalism and Modernity shares innovative research and charts new areas of analysis from an array of scholars in the field. Delving into a wide range of theoretical and conceptual perspectives, the essays - all previously unpublished - encompass social history, literary theory, postcolonial studies, and comparative analysis to address such topics as: Ethnicity in the Islamic Republic of Iran Political Islam and religious nationalism The evolution of U.S.-Iranian relations before and after the Cold War Comparing Islamic and secular nationalism(s) in Egypt and Iran The German counterrevolution and its influence on Iranian political alliances The effects of Israel's image as a Euro-American space Sufism Geocultural concepts in Azar's Atashkadeh Interdisciplinary in essence, the essays also draw from sociology, gender studies, and art and architecture. Posing compelling questions while challenging the conventional historiographical traditions, the authors (many of whom represent a new generation of Iranian studies scholars) give voice to a research approach that embraces the modern era's complexity while emphasizing Iranian nationalism's contested, multifaceted, and continuously transformative possibilities.